Potensi Pengembangan Kehutanan dan Pertanian Kabupaten Mahakam Ulu, Provinsi Kalimantan Timur - Omo Rusdiana; Supijatno Supijatno; Yanto Ardiyanto; Candraningratri Ekaputri Widodo (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Mahakam Ulu Regency is a new autonomous region formed separated from Kutai Barat regency of East Kalimantan Province in 2013. The local government of Mahakam Ulu has set to develop their local economy by utilizing and developing local resources. The regency’s geographical position at the northern border of Indonesia, together with its majority land coverage of natural forests, urges Mahakam Ulu to define its potential economic activities that support its people’s welfare and preserve its nature at the same time. This research aims to understand the regional development potential of Mahakam Ulu Regency on the forestry and agriculture sector, as well as to define strategies for development. Competitive commodities analysis, land suitability analysis and land availability analysis for the competitive commodities were conducted to obtain accurate information on the region’s forestry and agriculture potential. Analysis shows that Mahakam Ulu regency has forestry potentials in the form of development of community forest with non-timber forest products (NTFP) as the main commodity, environment service business in the form of ecotourism, utilization of timber forest products and NTFP, as well as development of customary forests. On the other side, potential agricultural commodities in Mahakam Ulu regency covers paddy, rubber, cacao and oil palm.